2007
DOI: 10.1080/00207590701251721
|View full text |Cite
|
Sign up to set email alerts
|

At the doorstep to employment: Discrimination against immigrants as a function of applicant ethnicity, job type, and raters' prejudice

Abstract: This study examined the impact of applicant ethnicity, job type, and prejudice on evaluation biases and intentions to interview in an experimental simulation. We suggest that bias and discrimination are more likely when foreign applicants who belong to disliked ethnic groups apply for jobs that require high interpersonal skills, and when raters are prejudiced against immigrants. Subjects were Swiss university students who evaluated Swiss, Spanish, and Kosovo Albanian fictitious applicants. Foreign applicants w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 19 publications
(35 reference statements)
2
31
0
2
Order By: Relevance
“…The four largest immigrant groups are people from ex-Yugoslavia, Italians, Portuguese, and Germans. The first group has come to Switzerland comparatively recently (mainly in the 1990s) and probably faces the most discrimination (e.g., Krings & Olivares, 2007). Of further note are the extensive naturalization requirements and procedures.…”
Section: Switzerlandmentioning
confidence: 99%
“…The four largest immigrant groups are people from ex-Yugoslavia, Italians, Portuguese, and Germans. The first group has come to Switzerland comparatively recently (mainly in the 1990s) and probably faces the most discrimination (e.g., Krings & Olivares, 2007). Of further note are the extensive naturalization requirements and procedures.…”
Section: Switzerlandmentioning
confidence: 99%
“…Frazer and Wiersma (2001) showed that Black candidates were evaluated less positively than White candidates after the interview had been conducted. Also, field (Bertrand and Mullainathan, 2004) and laboratory experiments (Krings and Olivares, 2007) show that majority candidates have higher chances to access and continue the hiring procedure than minority candidates. The discrepancies in results suggest that discrimination depends on additional factors, i.e., factors that moderate the extent of bias against minority candidates.…”
Section: Discrimination In Personnel Selection Decisionsmentioning
confidence: 96%
“…Ces deux secteurs d'emploi sont ceux pour lesquels les fonctions requises par le poste se caractérisent principalement par un service offert, non pas aux clients (marketing, communications et service à la clientèle), mais plutôt à d'autres employés ou membres du personnel de gestion au sein de l'organisation. Certaines études ont montré par le passé que les recruteurs sont davantage susceptibles d'adopter des pratiques discriminatoires lorsque le poste à combler suppose un contact avec la clientèle, par comparaison avec les postes à caractère plus technique ou manuel (Krings et Olivares, 2007 ;Pager, Western et Bonikowski, 2009). À la lumière de nos propres résultats, il semblerait que les membres de minorités racisées soient même encore plus à risque de subir la discrimination lorsque le poste suppose principalement des interactions fréquentes avec les autres employés ou les gestionnaires dans le cadre d'une prestation de service dispensée à l'interne.…”
Section: Tableauunclassified